The Social and Political Aspects of Permanent Housing Provision for Earthquake Tsunami and Liquefaction Casualties in Palu City, Central Sulawesi - Nursamsir Nursamsir; Indar Ismail Jamaluddin; Muhammad Iqbal; Ismanto Ismanto (Magister Ilmu Administrasi Publik, 2022)
An earthquake that struck Palu City, Central Sulawesi Province on September 28, 2018 rose potential problems. One of them is the permanent housing (huntap) provision for 6,504 earthquake-affected households. With a descriptive qualitative approach, this research focuses on the social and political aspects of providing permanent housing for disaster victims. Public opinion, both conveyed by refugees targeted for permanent housing and NGO activists and media workers, is expected to improve the policy of providing permanent housing for earthquake victims in Palu. The public hopes that the houses built for earthquake victims are to replace their lost homes and function as a place for psychological recovery. Therefore, the social aspects of housing provision are essential to receive government priorities, such as guaranteeing a sense of security, comfort, and relocated land status. Assistance and advocacy for displaced victims to obtain their rights should be appreciated, exceptionally due to the lack of political function of Regional House of Representative Council (DPRD) roles in guarding disaster victims. Legislators are unable to make a greater effort due to their status as part of the regional government. Simultaneously, the mass media’s attention to housing provisions is still vital for the government to formulate, implement and evaluate its policies. This study also discovered conditions where local governments have limited authority to provide shelter for displaced victims. Centralized government authority forces local governments to rely on the president and his staff.